Boundedness of Rough Singular Integral Operators on Homogeneous Herz Spaces with Variable Exponents (Journal of Mathematical Study, 2020)
We establish the boundedness of rough singular integral operators on homogeneous Herz spaces with variable exponents. As an application, we obtain theboundedness of related commutators with BMO functions on homogeneous Herz spaces with variable exponents.
Keywords: Rough singular integral operator; commutator; Herz spaces with variable exponents; BMO spaces.